ナンキョク ショウワキチ ノ コウタイイキ ジシン データ ノ リヨウ ト コウカ ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; 久保, 篤規; クボ, アツキ; Kanao, Masaki; Kubo, Atsuki (1996)
P(論文) 「南極・昭和基地を中心とする広帯域地震データの利用と成果に関する研究小集会」が, 1996年1月25日に国立極地研究所にて開催され, 所内外から12名が参加した。広帯域地震観測の歴史・現状報告につづき, 昭和基地をはじめとする南極の広帯域地震データによる研究成果の発表が中心に行われた。短周期実体波形・走時解析による地殻・上部マントルの速度構造・異方性の研究, ならびに地球自由振動とPKP波等の走時解析による内-外核・最下部マントル境界の地震波速度異方性の研究が主に紹介された。最後にこれらの研究成果をふまえて, 今後のデータアーカイブ・公開の指針, および南極観測における将来計画についての検討がなされた。 A workshop on "Public Use and Scientific Study of Broadband Seismic Data at Syowa Station, Antarctica" was held on January 25,1996 at the National Institute of Polar Research, with 12 participants. The history and present status of seismic observations were reported, followed by presentations concerning scientific studies using broadband data in Antarctica. The main contributions are (1) studies of the velocity structure and anisotropy in the crust and upper mantle using short-period body waveforms and travel time data and (2) analyses of the heterogeneity and anisotropy of seismic wave velocity in the core and the lowermost mantle by using short period core phases and free oscillations of the Earth. Finally, discussions concerning data archiving, public use and future plans of the Japanese Antarctic Research Expedition (JARE) were conducted in regarding to the above scientific results. departmental bulletin paper